Digital marketing strategy for purchasing decisions at Rezeky Payet Medan - Gultom, Pesta; Januarty, Widalicin; Wilbert, Wilbert (Junal Ilmu Manajemen, 2025)
This study aims to determine the influence of social media and content marketing on purchasing decisions at Rezeky Payet Medan. Rezeky Payet Indonesia is known as a supplier of high-quality raw materials for the fashion industry in Medan. The method used in this study is quantitative descriptive, and population use in this study consists of consumers who have shopped at Rezeky Payet Medan, the exact number of whom cannot be determined. Due to the uncertain number of respondents, the researcher used the hair method, which is a method employed when the researcher does not know the exact population size. In this study, 120 respondents were obtained, while the sampling technique used was accidental sampling. Data testing analysis consists of descriptive classical assumption tests, multiple linear analysis, partial hypothesis tests (t-test) and simultaneous tests (f-test), as well as the coefficient of determination test. The analysis results show a positive significant influence, both partially and simultaneously, between social media and content marketing on purchasing decisions at Rezeky Payet Medan.